2019
DOI: 10.3390/antiox8100450
|View full text |Cite
|
Sign up to set email alerts
|

Anti-Oxidant Activity of Gallotannin-Enriched Extract of Galla Rhois Can Associate with the Protection of the Cognitive Impairment through the Regulation of BDNF Signaling Pathway and Neuronal Cell Function in the Scopolamine-Treated ICR Mice

Abstract: The antibacterial, anti-inflammatory, anti-metastatic/anti-invasion activities and laxative activity of Galla Rhois (GR) are well-known, although the neuropreservation effects of their extracts are still to be elucidated. To investigate the novel therapeutic effects and molecular mechanism of GR on alleviation of cognitive impairment, two different dosages of gallotannin-enriched GR (GEGR) were administered to Korl:ICR mice for three weeks, and to induce memory impairment, scopolamine (SP) was administered dur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
6
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 57 publications
1
6
0
1
Order By: Relevance
“…While overexpression of SEH increased cell death. These datas were also in agreement with previous reports that protecting endothelial cells and neurons from pro-inflammatory mediators induced apoptosis by MAPK or PI3/Akt or BDNF signaling pathway in ischemic brain tissue (Hung et al, 2017;Hao et al, 2018;Park et al, 2019). We speculate that TPPU may exert this effect by reducing ischemia-induced mitochondrial damage and therefore mitochondria-mediated apoptotic signaling (Rekuviene et al, 2017).…”
Section: Discussionsupporting
confidence: 93%
“…While overexpression of SEH increased cell death. These datas were also in agreement with previous reports that protecting endothelial cells and neurons from pro-inflammatory mediators induced apoptosis by MAPK or PI3/Akt or BDNF signaling pathway in ischemic brain tissue (Hung et al, 2017;Hao et al, 2018;Park et al, 2019). We speculate that TPPU may exert this effect by reducing ischemia-induced mitochondrial damage and therefore mitochondria-mediated apoptotic signaling (Rekuviene et al, 2017).…”
Section: Discussionsupporting
confidence: 93%
“…Hematomal and perihematomal regions are biochemically active environments that sustain oxidative damage following ICH [ 2 ]. OS is defined as an imbalance between the formation of strong oxidants and physiologic antioxidant capacity [ 3 ]. ROS such as oxygen free radicals (e.g., superoxide (O 2 − ) and hydroxyl radicals (OH − )) and nonradical compounds (e.g., hydrogen peroxide (H 2 O 2 ) and hypochlorous acid), as well as reactive nitrogen species (RNS; e.g., nitric oxide (NO)) and a variety of nitrogenous compounds produced as metabolic byproducts, are the major drivers of oxidative damage [ 4 ] to proteins, lipids, and nucleic acids, which can induce inflammation, autophagy, apoptosis, and destruction of the BBB.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, it causes oxidative stress and promotes neuronal apoptosis [15,44,45]. Therefore, scopolamine has been applied in animal models to elicit AD-like symptoms involving both cholinergic dysfunction and oxidative stress [15,18]. We first performed behavioral experiments using the Morris water maze test to detect the effect of Mep-S in scopolamine-challenged mice.…”
Section: Discussionmentioning
confidence: 99%
“…Considering the critical roles of oxidative stress in AD pathogenesis, MTDLs with antioxidant potency may be favorable for AD therapy. In fact, the development of anti-AD MTDLs with antioxidant activity has recently attracted much attention [15,18]. In a previous research, we reported a number of (-)-meptazinol-melatonin/serotonin hybrids with multiple pharmacological properties [19].…”
Section: Introductionmentioning
confidence: 99%